Microbiological monitoring of heater-cooler unit to keep free of Mycobacterium chimaera infection. (January 2019) - Chan, Tanee; Ling, Moi Lin; Teng, Siew Yan; Chiu, Kit Yi; James, Esther Magdalane
Introduction: The association of Mycobacterium chimaera infection in patients undergoing cardiopulmonary bypass (CPB) with the use of heater-cooler units (HCU) has been reported in various literature. We described microbiological monitoring and the extent of microbiological contamination of HCUs utilized in our centre and strategies employed to reduce the high microbial load. Methods: Since August 2016, we have been following the new Instructions for Use from the manufacturer for the cleaning and disinfection of three units of Stöckert 3T and four units of Stöckert 1T HCU at the National Heart Centre Singapore. Microbiological monitoring began in January 2017 and included acid-fast bacilli (AFB) culture, Pseudomonas aeruginosa, total colony and total coliform count. Methods, such as increasing disinfection frequency and making the HCU inactive by keeping it empty in storage, were used to reduce the high colony count. Results: All three units of Stöckert 3T and two units of Stöckert 1T were contaminated with Mycobacterium chimaera . Pseudomonas aeruginosa and total coliform count were consistently <1 colony-forming unit (CFU)/100 mL in every water sample of each HCU. High colony counts were encountered initially in all units. Step-up frequency of disinfection was found to be not as effective as keeping the HCU inactive in bringing the total colony count to an acceptable level. Conclusions: All monitoring and maintenance measures of HCUs need to be established and maintained to mitigate potential infection risks to patients. Strict adherence to all cleaning and disinfection processes and keeping the HCU inactive maintained the water quality of the HCU at acceptable levels.